Turtles in Malaysia: a review of conservation status and a call for research - Mohd Salleh, Mohd Hairul; Esa, Yuzine; Mohd Salleh, Sarahaizad; Mohd Sah, Shahrul Anuar (MDPI AG, 2022)
Approximately 356 species of turtles inhabit saltwater and freshwater habitats globally, except in Antarctica. Twenty-four species of turtles have been reported in Malaysia, four of which are sea turtles. The state of Terengganu harbored the highest number of turtles, with 17 different reported species. Based on the IUCN Red List, 29% of turtle species in Malaysia are critically endangered. In comparison, another 25% are classified as endangered. Likewise, CITES reported that 67% of Malaysia’s turtles are threatened, while 25% are classified as critically endangered. This review discusses the checklists, molecular genetics work, conservation status, recent trends, and recommendations for future research. Factors contributing to their population declines and current endangered status are also discussed.